2021
DOI: 10.3390/en14227620
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Hybrid Solar-Wind Potential for Industrial Decarbonization Strategies: Global Shift to Green Development

Abstract: The global energy mix is shifting from fossil fuels to combinations of multiple energy storage and generation types. Hybrid energy system advancements provide opportunities for developing and deploying innovative green technology solutions that can further reduce emissions and achieve net-zero emissions by 2050. This study examined the impact of an increasing share of wind and solar electricity production on reducing carbon intensity by controlling coal and lignite domestic consumption and the production of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(18 citation statements)
references
References 67 publications
1
17
0
Order By: Relevance
“…Thus, we agree with Destek and Sinha (2020) that countries should strive to reduce the share of fossil fuels in their energy mix and, in turn, increase the share of renewable energy sources. Moreover, we are in line with Rashid Khan et al (2021) that studied the impact of two renewable sources, wind and solar electricity, on carbon intensity in a large panel of countries between 1990 and 2017 in an ARDL bounds testing framework and concluded that carbon intensity declines with increasing shares of wind and solar energy in electricity production, while the reverse is true in the case of coal and lignite. For Baltic states (Estonia, Latvia and Lithuania), Štreimikienė, et al (2016) also argued that an increased share of renewables and improvements in energy efficiency have a direct impact on the economy's energy carbon intensity, as well as on the reduction of energy import dependency, energy balance of trade, and energy mix diversification.…”
Section: Discussionsupporting
confidence: 87%
“…Thus, we agree with Destek and Sinha (2020) that countries should strive to reduce the share of fossil fuels in their energy mix and, in turn, increase the share of renewable energy sources. Moreover, we are in line with Rashid Khan et al (2021) that studied the impact of two renewable sources, wind and solar electricity, on carbon intensity in a large panel of countries between 1990 and 2017 in an ARDL bounds testing framework and concluded that carbon intensity declines with increasing shares of wind and solar energy in electricity production, while the reverse is true in the case of coal and lignite. For Baltic states (Estonia, Latvia and Lithuania), Štreimikienė, et al (2016) also argued that an increased share of renewables and improvements in energy efficiency have a direct impact on the economy's energy carbon intensity, as well as on the reduction of energy import dependency, energy balance of trade, and energy mix diversification.…”
Section: Discussionsupporting
confidence: 87%
“…However, there is still a need to further explore the internal or external factors which will affect TC and EC in the future in order to obtain a clearer understanding of the generation and elimination of interregional differences in DCEEIE. Finally, although increasing DCEEIE is an important way to reduce carbon emissions, the most fundamental and effective way to achieve green development is to increase the use of hybrid and renewable energy sources and reduce the use of fossil fuels (Abbasi et al, 2021a;Khan et al, 2021). Therefore, future research should focus on how to trigger and accelerate the transformation of energy infrastructure from fossil fuel use to hybrid and clean energy use at the source.…”
Section: Discussionmentioning
confidence: 99%
“…The sustainable practices of CSR implementation require enterprises to consider stakeholders' interests, including consumers, society, and the environment, while performing their production operations (Golinska-Dawson and Spychała 2018; Awan et al, 2019;Yang et al, 2019;Ikram et al, 2021). In recent times, business firms have faced increasing internal and external coercion to enhance non-financial performance and different dimensions, such as environmental protection challenges, social welfare, employee interest, and acceptable employment practices (Awan et al, 2020;Bhutto et al, 2021;Cheng et al, 2021;Rashid Khan et al, 2021). Scholars have debated sustainability issues converged by various stakeholders, policymakers, and investors (Begum et al, 2021a;Begum et al, 2021b;Ikram et al, 2021;Awan and Sroufe 2022).…”
Section: Sustainable Practices Of Corporate Social Responsibility And...mentioning
confidence: 99%